Sumber Daya Alam: Musibah atau Penghargaan (Studi Kasus Provinsi Jawa Timur 2013–2022) - Rofik, Mohammad; Darul Firmansyah, Imam; Ghufrony, Ahmad (PPJP ULM, 2024)
East Java is undoubtedly a region rich in natural resources, as Indonesia has long been known as a country with abundant natural resources. East Java is one of the provinces in Indonesia that has abundant natural resources. Plantations/agriculture, fisheries and marine resources, mining and energy, forestry, and livestock are some examples of these natural resources. There is one surprising fact that naturally a region that has abundant wealth is an advantage for the region, but sometimes the natural wealth of a region can be a blessing and a burden. Panel data regression is used in the study to test three elements: unemployment, poverty, and gross regional domestic product (GRDP) using three approach models in panel data regression analysis, namely the Common Effect, Fixed Effect and Random Effect models, which are then selected from the three models as the best model that can explain the results of the study. The conclusion of the data analysis shows that although the gross regional domestic product of East Java Province has a positive effect on unemployment and a negative effect on poverty.